Crashworthiness of G4(2W) guardrail system: a finite element parametric study. Issue 2 (4th March 2017) - Soltani, Mehrtash; Topa, Ameen; Karim, Mohamed Rehan; Sulong, N.H. Ramli
ABSTRACT: In recent years, vehicle demographics have changed to include a relatively large proportion of light trucks, such as pickups, vans and sport-utility vehicles. It is found that several types of guardrail systems, including the G4(2W) guardrail system, are unable to redirect the pickup trucks to roadway safely. Therefore, in this study, several options are considered; they include improving the splice connections and adjusting the guardrail height and the post spacing to improve the performance of this system. The G4(2W) guardrail system is modelled in LS-DYNA and validated with a previous full-scale crash test conducted by the Texas A&M Transportation Institute. A parametric study based on the results of the LS-DYNA crash simulation according to Length of Need test 3-11 and 3-10 is conducted to investigate key factors of guardrail systems, including the splice configuration, the post spacing and the guardrail height. The purpose of this study is to find a model that satisfies the requirements of Test Level 3 outlined in Manual for Assessing Safety Hardware (MASH)'s criteria.